Two new stilbenoids from the whole herb of Sphaerophysa salsula. (October 2018) - Jiao, Li Jin; Wang, Wei Dong; Tao, Yan Duo; Shao, Yun; Mei, Li Juan; Liu, Zeng Gen; Wang, Qi Lan; Dang, Jun
Graphical abstract: Highlights: Two new stilbenoid derivatives were isolated from Sphaerophysa salsula . One compound were isolated for the first time from this species. Eight known compounds were isolated from the plant. These compounds enriched the structural types of natural products from Sphaerophysa salsula . Abstract: Two new compounds, gnetuhainins Fa (1 ) and cassigarols Ea (2 ), were isolated from the whole herb of Sphaerophysa salsula along with eight known compounds (3 -10 ). The compounds (4 ) were isolated for the first time from this species. Their structures were elucidated by ESI-MS, UV, IR, 1D NMR and 2D NMR data.